A Roblox-Based VR Game in Chemistry: Development and Impact on Student Learning - Besse Firanita Astari; Sri Yamtinah; Eka Budhi Santosa (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2026)
This study developed and evaluated Mol Concept Adventure, a Roblox-based Virtual Reality (VR) game for teaching the mole concept in high school chemistry. The development followed the 4D model and involved 256 students and three teachers from three public schools in Southeast Sulawesi, Indonesia. The product was refined through expert validation and iterative testing. Expert judgment confirmed high content validity (Aiken’s V > 0.80), while psychometric analyses established adequate construct validity and reliability of the research instruments. A quasi-experimental study involving 160 students demonstrated high practicality, as reflected in positive evaluations from students and teachers. Moreover, the experimental group (n = 87) showed significantly greater improvements in problem-solving skills (N-Gain = 61.03% vs. 18.3%; p < .001) and higher learning motivation (p = .029) than the control group (n = 73) receiving conventional instruction. Overall, the findings indicate that the developed Roblox-based VR game is a valid, reliable, practical, and effective instructional tool for enhancing both cognitive and affective outcomes in high school chemistry learning.